The origin of high d18O zircons: Marbles, megacrysts, and metamorphism - Cavosie, Aaron; Valley, J.; Kita, N.; Spicuzza, M.; Ushikubo, T.; Wilde, Simon (Springer, 2011)
The oxygen isotope ratios (d18O) of most igneous zircons range from 5 to 8‰, with 99% of published values from 1345 rocks below 10‰. Metamorphic zircons from quartzite, metapelite, metabasite, and eclogite record d18O values from 5 to 17‰, with 99% below 15‰. However, zircons with anomalously high d18O, up to 23‰, have been reported in detrital suites; source rocks for these unusual zircons have not been identified. We report data for zircons from Sri Lanka and Myanmar that constrain a metamorphic petrogenesis for anomalously high d18O in zircon. A suite of 28 large detrital zircon megacrysts from Mogok (Myanmar) analyzed by laser fluorination yields d18O from 9.4 to 25.5‰. The U-Pb standard, CZ3, a large detrital zircon megacryst from Sri Lanka, yields d18O=15.4 ± 0.1‰ (2 SE) by ion microprobe. A euhedral unzoned zircon in a thin section of Sri Lanka granulite facies calcite marble yields d18O=19.4‰ by ion microprobe and confirms a metamorphic petrogenesis of zircon in marble. Small oxygen isotope fractionations between zircon and most minerals require a high d18O source for the high d18O zircons. Predicted equilibrium values of ?18O(calcite-zircon)=2-3‰ from 800 to 600°C show that metamorphic zircon crystallizing in a high d18O marble will have high d18O. The high d18O zircons (>15‰) from both Sri Lanka and Mogok overlap the values of primary marine carbonates, and marbles are known detrital gemstone sources in both localities. The high d18O zircons are thus metamorphic; the 15-25‰ zircon values are consistent with a marble origin in a rock-dominated system (i.e.,low fluid(external)/rock); the lower d18O zircon values (9-15‰) are consistent with an origin in an external fluid-dominated system, such as skarn derived from marble, although many non-metasomatized marbles also fall in this range of d18O. High d18O (>15‰) and the absence of zoning can thus be used as a tracer to identify a marble source for high d18O detrital zircons; this recognition can aid provenance studies in complex metamorphic terranes where age determinations alone may not allow discrimination of coeval source rocks. Metamorphic zircon megacrysts have not been reported previously and appear to be associated with high-grade marble. Identification of high d18O zircons can also aid geochronology studies that seek to date high-grade metamorphic events due to the ability to distinguish metamorphic from detrital zircons in marble. © 2011 Springer-Verlag.